2013
DOI: 10.1155/2013/918136
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Canker-Resistant Transgenic Sweet Orange (Citrus sinensisOsbeck) Constitutively Overexpressing a Spermidine Synthase Gene

Abstract: Citrus canker disease caused by Xanthomonas citri subsp. citri (Xcc) is one of the most devastating diseases affecting the citrus industry worldwide. In our previous study, the canker-resistant transgenic sweet orange (Citrus sinensis Osbeck) plants were produced via constitutively overexpressing a spermidine synthase. To unravel the molecular mechanisms underlying Xcc resistance of the transgenic plants, in the present study global transcriptional profiling was compared between untransformed line (WT) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…These complex results suggested that there are complex interactions among multiple genes and the exogenously expressed genes. The magnitude of the number differentially expressed genes found in this study is similar to previously reported ranges for transgenic plants harboring single transformation constructs [34,41,42]. …”
Section: Discussionsupporting
confidence: 90%
“…These complex results suggested that there are complex interactions among multiple genes and the exogenously expressed genes. The magnitude of the number differentially expressed genes found in this study is similar to previously reported ranges for transgenic plants harboring single transformation constructs [34,41,42]. …”
Section: Discussionsupporting
confidence: 90%
“…Consistent with these results, the increased production of hydrogen peroxide in sweet orange plants overexpressing an apple spermidine synthase gene (MdSPDS1) paralleled with the increased resistance to X. citri and augmented expression of defense-related genes (Fu et al 2011;Fu and Liu 2013). These results are also in agreement with the fact that canker symptoms attenuation in the transgenic plants overexpressing tobacco FLS2 or pepper Bs2 was concordant with an increase in ROS production (Hao et al 2016;SendĂ­n et al 2017).…”
Section: Defense-related Genessupporting
confidence: 78%
“…However, sweet orange plants modified in the same way were characterized by enhanced plant tolerance to Xanthomonas axonopodis pv. citri (Fu and Liu, 2013 ). Furthermore, overexpression of the SPMS gene in A. thaliana resulted in an increased spermidine content and enhanced resistance against Pseudomonas viridiflava (Gonzalez et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%